2020
DOI: 10.1109/access.2020.3007928
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Marine Predators Algorithm With Fuzzy Entropy for Multi-Level Thresholding: Real World Example of COVID-19 CT Image Segmentation

Abstract: Medical imaging techniques play a critical role in diagnosing diseases and patient healthcare. They help in treatment, diagnosis, and early detection. Image segmentation is one of the most important steps in processing medical images, and it has been widely used in many applications. Multi-level thresholding (MLT) is considered as one of the simplest and most effective image segmentation techniques. Traditional approaches apply histogram methods; however, these methods face some challenges. In recent years, sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 92 publications
0
51
0
Order By: Relevance
“…With the fast propagation of COVID-19, several researchers presented many solutions for the detection and segmentation of chest CT gray-level images. In [ 13 ], the authors proposed a new version of the marine predator’s algorithm (MPA) improved by MFO based on fuzzy entropy. The proposed method MPAMFO presented their efficiency compared to the existing swarm intelligence works in terms of PSNR and SSIM.…”
Section: Related Workmentioning
confidence: 99%
“…With the fast propagation of COVID-19, several researchers presented many solutions for the detection and segmentation of chest CT gray-level images. In [ 13 ], the authors proposed a new version of the marine predator’s algorithm (MPA) improved by MFO based on fuzzy entropy. The proposed method MPAMFO presented their efficiency compared to the existing swarm intelligence works in terms of PSNR and SSIM.…”
Section: Related Workmentioning
confidence: 99%
“…It is invasive and time-consuming, and the diagnosis is false-negative. Chest computed tomography (CT) is another test that plays an essential role in COVID-19 diagnosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies suggested that chest CT has a high detection sensitivity for COVID-19 lung pathology. Several groups have demonstrated the capacity for diagnosis based on CAD systems, with accuracy as high as 95% [ 7 ]. Medical imaging has been used recently for multiple diagnoses of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosing COVID-19 is a critical challenge for health organizations that must be accurately and efficiently implemented to make necessary plans [3]. The real-time polymerase chain reaction (RT-PCR) can be used to diagnose COVID-19, but it is a time-consuming test; also, it may suffer from false-negative diagnosing [4,5]. Therefore, medical imaging, such as chest X-ray and chest Computed Tomography (CT) can be used efficiently for diagnosing Image segmentation is considered as an important key for analyzing medical images.…”
Section: Introductionmentioning
confidence: 99%